2019
DOI: 10.3390/su11216165
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-Agronomic Characterisation of Runner Bean (Phaseolus coccineus L.) from South-Eastern Europe

Abstract: In South-Eastern Europe, the majority of runner-bean (Phaseolus coccineus L.) production is based on local populations grown mainly in home gardens. The local runner-bean plants are well adapted to their specific growing conditions and microclimate agro-environments, and show great morpho-agronomic diversity. Here, 142 runner-bean accessions from the five South-Eastern European countries of Slovenia, Bosnia and Herzegovina, Serbia, North Macedonia and Romania were sown and cultivated in their respective countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 29 publications
4
7
0
Order By: Relevance
“…In this context, line 3 showed an average of 4.9 seeds per pod, which was significantly ( p > 0.05) higher than the rest of the lines evaluated, which varied between 1.7 (line 19) to 3.2 (line 1) seeds per pod. This result is in accordance with a previous study by Sinkovic et al [ 15 ], who indicated that most of the accessions from South Eastern Europe had 2–3 seeds per pod. In addition, the average number of seeds per pod in a wild population of runner bean was 4.2 [ 40 ].…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…In this context, line 3 showed an average of 4.9 seeds per pod, which was significantly ( p > 0.05) higher than the rest of the lines evaluated, which varied between 1.7 (line 19) to 3.2 (line 1) seeds per pod. This result is in accordance with a previous study by Sinkovic et al [ 15 ], who indicated that most of the accessions from South Eastern Europe had 2–3 seeds per pod. In addition, the average number of seeds per pod in a wild population of runner bean was 4.2 [ 40 ].…”
Section: Resultssupporting
confidence: 94%
“…The runner bean is characterized by an indeterminate type of growth [ 4 ], which coincides with our results where all the lines exhibited an indeterminate growth type, excepting line 3, which 50% of the plants showed a determined growth habit ( Table 1 ). Similar results were reported by Sinkovic et al [ 15 ], who evaluated a population of 142 accessions of runner bean from South Eastern Europe, and almost all of accessions (excepting three) exhibited an indeterminate plant growth. In addition, Sicard et al [ 27 ] evaluated nine local varieties of P. coccineus from Eastern Italy, and all the varieties showed an indeterminate plant growth.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations